Processing of Emotions in Functional Movement Disorder: An Exploratory fMRI Study - Sojka, Petr; Lošák, Jan; Lamoš, Martin; Bareš, Martin; Kašpárek, Tomáš; Brázdil, M.; Baláž, M.; Světlák, Miroslav; Kočvarová, J.; Fialová, J. (Frontiers in Neurology, 2019)
Background: Affective dysregulation and impaired cognitive control are implicated in the pathology of functional neurological disorders. However, voluntary regulation of emotions has seldom been researched in this group of patients. We hypothesized that patients with functional neurological disorders use inefficient voluntary emotion regulation strategies and regulate emotional reactions via increased motor activation. Methods: Fifteen patients with functional movement disorder and 15 healthy subjects matched by age, sex. and education underwent an emotion regulation task in fMRI. For stimuli, we used neutral and negative pictures from the International Affective Picture System. There was no restriction on their emotion regulation strategy. Both patients and healthy subjects were asked about the strategies they had used in a post-scanning interview. Participant levels of depression, trait anxiety, and alexithymia were assessed. Results: There were no significant differences in the emotion regulation strategies used by patients and healthy subjects, nor in levels of reported alexithymia and depression. However, patients showed increased activation in several brain areas when observing negative pictures, notably in the postcentral gyrus, precuneus, posterior cingulate cortex, and cerebellar vermis, and also in their emotion regulation condition, particularly in the precuneus and postcentral gyrus. Alexithymia was negatively associated with left insular activation during the observation of unpleasant stimuli only in the patient group. Conclusions: Our findings may implicate a role of areas associated with self-referential processing in voluntary emotional regulation and lower emotional awareness in patients with functional movement disorders. However, our findings must be replicated with larger sample.